2009
DOI: 10.1128/cvi.00218-09
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Infection of Reindeer with Cervid Herpesvirus 2

Abstract: Cervid herpesvirus 2 (CvHV2) has been isolated from reindeer (Rangifer tarandus tarandus), and serological data indicate that in reindeer this virus is endemic in Fennoscandia, Alaska, Canada, and Greenland. CvHV2 has been described as a cause of subclinical genital infections in reindeer, but little information on primary infections exists. In this study, six seronegative and presumably pregnant reindeer were allocated to one of two groups. Two animals were inoculated with CvHV2 intratracheally, and two anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…This is in line with previous inoculation experiments in reindeer with CvHV2 [36], in which a humoral immune response generally was not evident until days 8–10 p.i. Thus, the rapid onset of clinical signs after inoculation of CvHV2 in the conjunctiva indicates that a primary specific immune response will develop too late to be protective against disease in previously unexposed animals.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with previous inoculation experiments in reindeer with CvHV2 [36], in which a humoral immune response generally was not evident until days 8–10 p.i. Thus, the rapid onset of clinical signs after inoculation of CvHV2 in the conjunctiva indicates that a primary specific immune response will develop too late to be protective against disease in previously unexposed animals.…”
Section: Discussionsupporting
confidence: 92%
“…Recent reports have revealed that latent infections might be activated by glucocorticosteroids, and that infections are associated to mucosal lesions in the gastro-intestinal tract. Further, CvHV2 can be transferred from mother to the foetus, can cause abortion and also possibly serve as the contagious component in the disease etiology of infectious keratoconjunctivitis (IKC) (Das Neves et al, 2009b;Tryland et al, 2009). CvHV2 infections may gain increased importance if animal density and general stress load of animals increases (Das Neves et al, 2009a).…”
Section: Changes In Reindeer Herdingmentioning
confidence: 99%
“…In a previous experimental infection with CvHV2 in reindeer, where the animals were inoculated intratracheally or intravaginally [29], immunohistochemistry for CvHV2 of lung and uterine tissues showed strong positive staining of goblet cells of the respiratory epithelium and basal cells of endometrial glands. Positive virus staining was also observed in leukocytes.…”
Section: Discussionmentioning
confidence: 81%
“…This virus tropism is consistent with the severe epithelial and glandular damage described in the eye tissues in the present study, and with our observation of enveloped viral particles and viral capsids in the necrotic eye tissue, and viral capsids inside a neutrophil, by electron microscopy ( Figure 5). Unfortunately, the monoclonal antibodies used in the study by das Neves et al [29] are no longer available.…”
Section: Discussionmentioning
confidence: 99%